Density Functional Theory (DFT) Calculation Of Band Structure Of Kesterite - Katrul Nadia Basri; Noriza Ahmad Zabidi; Hasan Abu Kassim; Ahmad Nazrul Rosli (Scientific.net, 2024)
The kesterite, Cu2ZnSnS4 has a big potential as a future solar material in replacing current material. Although the kesterite and copper indium gallium selenide, CIGS has almost same structure but the constituent elements of kesterite are earth-abundance, cheaper and non-toxic. The chalcogen elements existed inside the kesterite compound are selenium and sulphur, Cu2ZnSnSe4 / Cu2ZnSnS4. Therefore, the structural flexibility of kesterite opens up an avenue to develop light-absorber material with suitable properties and applications. The density functional theory (DFT) has been used to calculate the total energy of Kesterite developed from Material Studio - CASTEP. The general gradient approximation (GGA) has been choosing to treat the exchange-correlation. The structure of kesterite has been developed by determining its space group, I4 and Pc and its coordination of each atom. The previous calculated shown that the energy of its band gap is around 1.0-1.5 eV.